Development of intellectual and creative competence of future teachers - Abduvalieva, Dilsora N. (Vestnik of Samara State Technical University Psychological and Pedagogical Sciences, 2022)
The intellectual and creative competence of a teacher directly determines his competitiveness in the professional sphere and his readiness to use his intellectual experience for the benefit of the future of his country. Thus, the specification of the essence of the component composition of intellectual competence and the description of its components seem to be extremely relevant in the light of the problem being solved. The paper analyzes the component composition of future teachers intellectual and creative competence. The necessity of the work done is explained by the fact that the competences mentioned includes all the main elements of the content of education: general educational skills, meta-knowledge, and over-subject activities. The studied intellectual and creative competence is the basis of the individual style of students cognitive activity, which underlies their future professional activity. The paper discusses various approaches to determining the structure of this competence, presented in the works of major researchers. The analysis made it possible to identify the following components of intellectual and creative competence: motivational value, cognitive, communicative, metacognitive, research, self-educational, and personal.